Coordinated Management and Control Strategy in the Low-Voltage Distribution Network Based on the Cloud-Edge Collaborative Mechanism - Gao, Jiuguo; Lu, Yang; Wu, Bin; Zheng, Ting; Zhu, Yu; Zhang, Zhixiang (Frontiers in Energy Research, 2022)
With the gradual increase in the deployment of distributed power sources and electric vehicles, the coordinated dispatch of clean power is of great significance to improve the economics of electricity consumption by prosumers and promote the consumption of renewable energy. On the basis of considering photovoltaic as a shared power resource, a low-voltage distribution network electric vehicle and distributed photovoltaic coordinated management and control strategy was proposed, and a day-ahead dispatch model of photovoltaic and electric vehicles for prosumers was established, which also considered the total cost of electricity consumption and two targets for photovoltaic consumption. The NSGA-2 algorithm is used to solve the model to obtain the Pareto optimal solution set, and the satisfaction evaluation method is used to select the optimal compromise solution. Based on the cloud-edge collaborative mechanism, the aforementioned technologies are deployed in the intelligent perception terminal device to execute downward computing, storage, and resource management strategies of the cloud station. A 24-period simulation calculation was performed on a low-voltage distribution network with 20 households. The results show that the proposed collaborative management and control strategy is beneficial to improve the economic efficiency of users’ electricity consumption and promote the consumption of clean energy.